Theoretical Basis of Outsourcing - Kovalyov, A.V. (Економічний вісник Донбасу, 2013)
The present paper contains the analysis of the existing classifications of types of outsourcing. It demonstrates that these classifications are based on managerial and organizational criteria without taking into account the economical nature of outsourcing. Differences between outsourcing and purchase of products and services are described. A new approach to outsourcing is proposed that is based on economical aspects of this phenomenon. New classifications of types of outsourcing based on its economical nature and the types of interaction between companies are given. A list of methods of payment for outsourcing services is applied.